PERANCANGAN SISTEM INFORMASI PENOMORAN SURAT DIGITAL PADA PTSP KANWIL KEMENAG SUMSEL DENGAN METODE PROTOTIPE - Putri Maharani; Freddy Kurnia Wijaya (CV. Denasya Smart Publisher, 2026)
Administrative services in government institutions require fast, accurate, and well-documented processes. At the Integrated One-Stop Service (PTSP) of the Regional Office of the Ministry of Religious Affairs of South Sumatra, the letter numbering process is still carried out manually, resulting in delayed document issuance, numbering duplication, recording errors, and difficulties in tracking and archiving documents. This study aims to design a web-based digital letter numbering information system capable of automating the process of assigning letter numbers, storing digital archives, as well as searching and tracking official documents to improve administrative performance. The prototype method was applied through several iterative stages including identifying user needs, designing system prototypes, collecting user feedback, improving features based on evaluations, and testing functionality. The results show that the developed system can automatically generate structured and non-duplicated letter numbers, store letter archives digitally, accelerate document retrieval through keyword search and preview features, and visualize statistical reports of issuance data through graphical dashboards. Role-based dashboard separation between employees and administrators ensures data security and system flexibility, while the Help and Complaint features support practical feedback and issue reporting. System testing indicated that all functions run well without major errors, suggesting the system is ready for limited implementation. Overall, the digital letter numbering information system successfully improves administrative efficiency, service speed, and supports digital-based public service modernization in PTSP.